Metabolic Syndrome and Outcomes after Renal Intervention - Daynene Vykoukal; Mark G. Davies (Cardiology Research and Practice)
Metabolic syndrome significantly increases the risk for cardiovascular disease and chronic kidney disease. The increased risk for cardiovascular diseases can partly be caused by a prothrombotic state that exists because of abdominal obesity. Multiple observational studies have consistently shown that increased body mass index as well as insulin resistance and increased fasting insulin levels is associated with chronic kidney disease, even after adjustment for related disorders. Metabolic syndrome appears to be a risk factor for chronic kidney disease, likely due to the combination of dysglycemia and high blood pressure. Metabolic syndrome is associated with markedly reduced renal clinical benefit and increased progression to hemodialysis following endovascular intervention for atherosclerotic renal artery stenosis. Metabolic syndrome is associated with inferior early outcomes for dialysis access procedures.